Identification of impurities in nafamostat mesylate using HPLC-IT-TOF/MS: A series of double-charged ions - Yuxin Zhang; Lufan An; Lin Zhang; Rulin Wang; Yuan Tian; Zunjian Zhang (Elsevier, 2020)
Nafamostat mesylate is a serine protease inhibitor used in the treatment of acute pancreatitis. The impurities in nafamostat mesylate, the active pharmaceutical ingredient (API), were profiled via high performance liquid chromatography tandem ion trap coupled with time-of-flight mass spectrometer (HPLC-IT-TOF/MS). The chromatography was performed on an ACE-3 C18 column (200 mm × 4.6 mm, 3 μm) using methanol and 0.1% formic acid in purified water as mobile phase at a flow rate of 1.0 mL/min. The ions were detected by IT-TOF/MS with a full-scan mass analysis from m/z 100 to 800. In total, eleven impurities were detected in nafamostat mesylate API. The impurity profile was estimated based on the HPLC-IT-TOF/MS data, including accurate masses, MSn fingerprints of fragmentation pathways and a series of double-charged ions. Finally, seven impurities were identified and reported for the first time. The results will provide technical support for the quality control and clinical safety of nafamostat mesylate.